Influence of elements of cultivation technology on yield and grain quality of winter triticale in the conditions of the Urals - Sukhanberdina, L. Kh.; Tulegenova, D. K.; Kaliyeva, L. T.; Turbayev, A. Zh.; Mussina, M. K. (IOP Conference Series: Earth and Environmental Science: International Scientific and Practical Conference on Improving Energy Efficiency, Environmental Safety and Sustainable Development in Agriculture: EESTE 2021, 2021)
The article presents the results of experimental studies to identify the optimal sowing dates and seeding rates for seeds of winter triticale varieties. Grain yield indicators at different sowing dates and seeding rates for 2019-2020 indicate that 2020 was more favorable for the formation of high productivity of winter triticale. Analysis of two-year data on the productivity of winter triticale varieties showed that with a late sowing period (September 15), a decrease in productivity is observed. The use of an increased seeding rate leads to an increase in the density of the productive stalk, with a simultaneous decrease in the mass of grain in the ear and the grain content in the ear. Favorable conditions were created for plants of the first (August 25) and second (September 5) sowing dates, with a seeding rate of 3.0 million and 4.0 million germinating grains per hectare. It was revealed that, regardless of the seeding rate, an increase in the level of protein in the grain of triticale varieties occurs at a late sowing period (September 15). The maximum protein content was noted in the Kastus variety (15.1%) at the third sowing period, at a seeding rate of 3.0 million germinating grains per hectare. To obtain high and stable yields of winter triticale grain in local conditions, the optimal sowing period should be considered the period from august 25 to September 5, at a seeding rate of 3.0 and 4.0 million germinable grains per hectare. With a favorable regime of moisture supply, it is allowed to sow winter triticale until September 15. The use of an increased rate (5.0 million) is not a factor contributing to an increase in yields in winter triticale varieties under WKO conditions. The most productive varieties adapted to the conditions of the dry steppe zone are the varieties Kastus, Fidelio, Valentin 90, which can be recommended for introduction into production В статье представлены результаты экспериментальных исследований по выявлению оптимальных сроков посева и норм высева семян сортов озимого тритикале. Показатели урожайности зерна при разных сроках посева и нормах высева за 2019-2020 годы свидетельствуют о том, что 2020 год был более благоприятным для формирования высокой продуктивности озимого тритикале. Анализ двухлетних данных по урожайности сортов озимой тритикале показал, что при позднем сроке посева (15 сентября) наблюдается снижение урожайности. Применение повышенной нормы высева приводит к увеличению густоты продуктивного стебля при одновременном снижении массы зерна в колосе и зернистости в колосе. Благоприятные условия были созданы для растений первого (25 августа) и второго (5 сентября) сроков сева при норме высева 3,0 млн и 4,0 млн всхожих зерен на 1 га. Выявлено, что независимо от нормы высева повышение уровня белка в зерне сортов тритикале происходит при поздних сроках посева (15 сентября). Максимальное содержание белка отмечено у сорта Кастусь (15,1 %) в третий период посева при норме высева 3,0 млн всхожих зерен на 1 га. Для получения высоких и стабильных урожаев зерна озимого тритикале в местных условиях.
Keywords: импакт-фактор 2022; скопус; scopus; конференции; дальнее зарубежье; тритикале; кормовые культуры; зко